Legal Protection of Historical Sites and Cultural Artifacts in Poland and Jordan - Alkhasawneh, Alaeldin; Kowalska, Samanta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2025)
Cultural heritage is created the axiological foundation of society. The pillars of each nation and ethnicity are built on traditional values and the legacy of ancestors passed from generation to generation. The aim of this article is to discuss the legal protection of historical sites and cultural artifacts in the light of Polish and Jordanian law. For this purpose, the arguments are supplemented with a comparative methodology. The Jordanian legislator adopted two concepts of antiquities–one broad and including any immovable or movable property that the state considers an antiquity, and the other narrow, limiting antiquities to what was created by humans. Since Jordan considers antiquities to be the public property of the state, they may not be seized or disposed of by sale or mortgage; individual ownership of antiquities is an exception, and the state places many restrictions on them. In Polish law, among the forms of protection of monuments, considerations are focused on entry into the register of monuments, recognition as historical monuments, and protection that affects the status of monuments. The article will provide examples of implementing provisions on bilateral cooperation between Poland and Jordan, in particular, in the cooperation developing in the sphere of culture.